Analisis Implementasi Total Quality Management dan Tingkat Risiko Produksi Sambal Bu Sandra Surabaya - Wahyu Halya Aprilia Putri; Teguh Soedarto; Prasmita Dian Wijayati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The agroindustry plays a crucial role in supporting food security, providing employment opportunities, and stimulating local economic growth. Sambal Bu Sandra is one of the agroindustries in Surabaya that processes agricultural products into packaged chili sauce. To sustain the business amidst competition and production uncertainty, effective quality management and risk mitigation in production are essential. This study aims to analyze the implementation of Total Quality Management (TQM) and assess production risk levels in Sambal Bu Sandra. The variables include: (1) the implementation of TQM, which consists of ten elements: customer focus, obsession with quality, scientific approach, long term commitment, teamwork, continuous improvement, education and training, controlled freedom, unity of purpose, and employee engagement and empowerment; and (2) the production level of chili sauce. The research was conducted from April to May 2025, employing a mixed-methods approach. Data were collected through company documentation, observations, questionnaires, and in-depth interviews with 10 purposively selected informants. TQM was analyzed descriptively using the average Likert scale score per element, identifying the highest and lowest contributing elements. Production risk was assessed quantitatively using the coefficient of variation (CV) and the lower production limit (L), calculated with Microsoft Excel 2021. Results show that the implementation of TQM reached 86.33%, with the highest contribution from employee involvement and empowerment (9.39%) and the lowest from continuous improvement (7.55%). The production risk was relatively low, indicated by a CV value of 0.27 and a lower production limit of 437.45 units. These results highlight the practical importance of strengthening written SOPs and adopting a digital-based quality control system to improve operational efficiency and reduce production risk in Sambal Bu Sandra Surabaya.